The Problem in the Issue of Marriage is Scary and Childfree in Indonesia - Hilma Nur Ashlaksha; Syafik Muhammad; Apik Anitasari Intan Saputri; Misbahul Huda (Journal Of Legal Studies Judex Praetor, 2025)
The phenomenon of marriage is scary and childfree is increasingly attracting attention, especially in Indonesia, especially among the younger generation. Many individuals are starting to doubt marriage and the decision to have children due to various factors including economic, social and psychological factors. Fear of marriage (marriage is scary) is often associated with increasing divorce rates, financial instability and social and cultural pressures that still maintain traditional roles in the household, while the choice to not have children (childfree) arises as a response to economic challenges, high living costs and the desire to obtain personal freedom and well-being. In Indonesia, the debate regarding these two issues is quite complex because cultural norms and religious teachings still place marriage and children as part of an ideal life, individuals who choose to postpone or avoid marriage and those who decide to live without children often face social pressure and pressure from family and the surrounding environment, however, changes in mindsets and increasing awareness of individual rights in determining their life path are starting to open up a wider discussion space regarding the concept of family and happiness in the modern era. This study aims to analyze the factors that influence fear of marriage and the decision not to have children in Indonesia. By understanding this trend, it is hoped that a new perspective can be obtained regarding the diversity of life choices and their impact on social dynamics and family structures in the future.